2015
DOI: 10.1021/acs.jpcc.5b08903
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Application of Ag44 Clusters Supported on Mesoporous Carbon

Abstract: 4-(Fluoro­phenyl)­thiolate-protected Ag44 clusters (Ph4P)4[Ag44(SC6H4F)30] were calcined on mesoporous carbon (MPC) under vacuum at 300–500 °C for 2 h. X-ray absorption spectroscopy, transmission electron microscopy, and thermal-desorption mass spectrometry revealed that sulfur-free Ag44 clusters were successfully produced by the calcination of [Ag44(SC6H4F)30]4– at 300 °C, in sharp contrast to the formation of silver sulfide nanoparticles by the calcination of dodecanethiolate-protected Ag nanoparticles (3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 62 publications
3
49
0
Order By: Relevance
“…However, in this case, instead of capping, the porous carbonaceous materials are usually used to support the NCs during the in situ synthesis. Moreover, externally synthesized NCs can also be dispersed to prevent sintering/migration during pyrolysis . During catalysis the use of conducting materials, such as graphene and CNTs, as support for NCs is an effective strategy.…”
Section: Synthesis Of Mncsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case, instead of capping, the porous carbonaceous materials are usually used to support the NCs during the in situ synthesis. Moreover, externally synthesized NCs can also be dispersed to prevent sintering/migration during pyrolysis . During catalysis the use of conducting materials, such as graphene and CNTs, as support for NCs is an effective strategy.…”
Section: Synthesis Of Mncsmentioning
confidence: 99%
“…Moreover,e xternallys ynthesized NCs can also be dispersed to prevents intering/migration during pyrolysis. [160] During catalysis the use of conducting materials, such as graphene and CNTs, as support for NCs is an effective strategy.I na ddition to the extended p-p interactions throughout graphene andd opingo fh eteroatoms functionalizations can further increase the number of defective sites and their trapping ability for the stabilization of small NCs (Scheme 8d). [161] In addition to solution-based chemistry (wet chemistry), various sputtering and ionization methods were also developed and usually adopted for the atom-by-atomd eposition in gas phase.…”
Section: Synthesis Of Ligand-/surfactant-free Mncsmentioning
confidence: 99%
“…Our work advances one step toward monitoring and understanding the cytotoxicity of thiolated silver nanoparticles.Silver nanoparticles (Ag NPs, including the ultrasmall nanoparticles, so-called nanoclusters, [1,2] and their larger counterparts, nanocrystals [3,4] )h ave been increasingly used for practical applicationsa nd research purposes, [5][6][7][8][9][10][11][12][13][14][15][16] owing to their relatively low cost (compared with Au, Pt, etc.) How to rapidly probe their cytotoxicity?, ands of orth.…”
mentioning
confidence: 99%
“…It is found that the cytotoxicity of silver nanoparticles is size dependent in the investigated size range, that is, with increasing size, the cytotoxicityi ncreases. Our work advances one step toward monitoring and understanding the cytotoxicity of thiolated silver nanoparticles.Silver nanoparticles (Ag NPs, including the ultrasmall nanoparticles, so-called nanoclusters, [1,2] and their larger counterparts, nanocrystals [3,4] )h ave been increasingly used for practical applicationsa nd research purposes, [5][6][7][8][9][10][11][12][13][14][15][16] owing to their relatively low cost (compared with Au, Pt, etc.) andi ntriguing physicochemicalp roperties (enhanced Ramans cattering, [17,18] bright fluorescence, [19,20] antimicrobial property, [21][22][23] etc.).…”
mentioning
confidence: 99%
“…a) Illustration of the cluster fabrication process using RTDPAs with 24 reducinge lectrons. STEM images and size dispersionso fb ,d) Ag24 and c,e) Pt 6 .…”
mentioning
confidence: 99%